Leaf Carbon Exchange of Two Dominant Plant Species Impacted by Water and Nitrogen Application in a Semi-Arid Temperate Steppe - Zhang, Xiaolin; Zhai, Penghui; Huang, Jianhui (Frontiers in Plant Science, 2022)
Photosynthetic characteristics are widely used as indicators of plant responses to global environmental changes such as precipitation change and nitrogen (N) deposition increase. How different plant species respond physiologically to the future precipitation change combined with increasing N availability is largely unclear. A field experiment was conducted to study responses in seasonal and interannual leaf carbon (C) exchange of two dominant plant species, Leymus chinensis and Stipa grandis, to additional water (either as spring snow or as summer water) and N application in a semi-arid temperate steppe of China. Our results showed that spring snow and summer water addition both increased the maximum photosynthetic rate (Amax) of two dominant species. Such effect was likely caused by raised light saturation point, the maximum apparent quantum yield, stomatal conductance, and transpiration rate. The N application combined with spring snow or summer water addition both enhanced Amax of S. grandis in both experimental years, whereas N application only increased Amax of L. chinensis combined with summer water addition. Their responses were attributed to a concurrent increase in leaf N concentration (Nleaf) and decrease in leaf phosphorus (P) concentration (Pleaf), indicating that Nleaf and Pleaf affect photosynthetic characteristics to regulate leaf C exchange. Our results suggest that differentiated responses among different species in photosynthetic characteristics may lead to changes in ecosystem structure and functioning under increasing precipitation and N deposition.